Desentralisasi Pelaksanaan Program Penaggulangan HIV/AIDS di Kota Makassar - Darmawansyah, Darmawansyah; Arifin, Muhammad Alwy; Abadi, Muh Yusri; Marzuki, Dian Saputra; Fajrin, Muhammad Al; Birawa, Rio Aristo; Rosdiana, Rosdiana (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2020)
The availability of qualified and professional health human resources (HRH) will greatly determine the success of implementing decentralization. This study aims to examine decentralization in the HIV / AIDS prevention program in Makassar City. This study uses a qualitative research method with a case study design. The informants in this study were the Chairperson of the Provincial AIDS Commission (KPAP) of South Sulawesi Province, the holder of the HIV-AIDS program at the Puskesmas, and the Head of the NGO organization concerned with HIV-AIDS in Makassar. The selection of informants in this study used the snowball technique. The data analysis technique in this study used qualitative data analysis. The results showed that human resources for the HIV / AIDS program in Makassar City had been fulfilled and were in accordance with the qualifications consisting of doctors, nurses, laboratories, pharmacists, and public health workers. Community empowerment in HIV / AIDS prevention has been running so that cadres are formed in the field but this empowerment has not been maximized in its implementation. In order for the decentralization of the HIV / AIDS prevention program to run optimally, stakeholder cooperation is needed in its implementation to run well to reduce cases of HIV / AIDS in Makassar City and it is necessary to strengthen the role of community empowerment in preventing the spread of HIV / AIDS cases. Keywords: Decentralization, Prevention Program, HIV / AIDS, Makassar City